2008
DOI: 10.1093/scan/nsn002
|View full text |Cite
|
Sign up to set email alerts
|

Learning affective values for faces is expressed in amygdala and fusiform gyrus

Abstract: To monitor the environment for social threat humans must build affective evaluations of others. These evaluations are malleable and to a high degree shaped by responses engendered by specific social encounters. The precise neuronal mechanism by which these evaluations are constructed is poorly understood. We tested a hypothesis that conjoint activity in amygdala and fusiform gyrus would correlate with acquisition of social stimulus value. We tested this using a reinforcement learning algorithm, Q-learning, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 44 publications
6
30
1
Order By: Relevance
“…with the social and emotional nature of our stimuli. Indeed, several fMRI studies have observed effects related to emotional memory mechanisms in early visual areas (Damaraju et al, 2009;Fenker et al, 2005;Padmala and Pessoa, 2008;Petrovic et al, 2008). Furthermore, the amygdala is at the core of a network that processes emotional stimuli of both negative and positive valence (Sergerie et al, 2008; see also Morrison and Salzman, 2010;Paton et al, 2006) and it also plays a central role in emotional memory (Buchanan, 2007;Dolan, 2007;Phelps and LeDoux, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…with the social and emotional nature of our stimuli. Indeed, several fMRI studies have observed effects related to emotional memory mechanisms in early visual areas (Damaraju et al, 2009;Fenker et al, 2005;Padmala and Pessoa, 2008;Petrovic et al, 2008). Furthermore, the amygdala is at the core of a network that processes emotional stimuli of both negative and positive valence (Sergerie et al, 2008; see also Morrison and Salzman, 2010;Paton et al, 2006) and it also plays a central role in emotional memory (Buchanan, 2007;Dolan, 2007;Phelps and LeDoux, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Recent neuroimaging studies have indeed shown that the emotional context associated with a neutral stimulus can influence the neural memory trace of that stimulus (Damaraju et al, 2009;Erk et al, 2005;Fenker et al, 2005;Galli et al, 2006;Keil et al, 2007;Padmala and Pessoa, 2008;Petrovic et al, 2008;Smith et al, 2005;Sterpenich et al, 2006;Stolarova et al, 2006;Todorov et al, 2007;Tsukiura and Cabeza, 2008). This influence has been observed throughout the visual processing stream, including striate and extrastriate regions (Damaraju et al, 2009;Fenker et al, 2005;Padmala and Pessoa, 2008;Petrovic et al, 2008) in line with the view that memory and perceptual processing are underpinned by the same mechanisms and involve shared neuronal systems (Brunel et al, 2009;Slotnick and Schacter, 2006; for a review see Graham et al, 2010). It is however unknown whether this reflects modulations of the earliest stages of visual processing: may an emotional influence be observed from the very first stages of visual processing?…”
Section: Introductionmentioning
confidence: 99%
“…In the largest study yet published on the neural basis of individual differences in fear conditionability ( n = 27), Petrovic and colleagues [21] sought to investigate neural mechanisms underlying affective evaluations of social stimuli. To this end, participants viewed pictures of 4 different faces over the course of an experiment.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Two of the faces (CS+) were paired with mild electric shock (US) on 50% of trials; the other two faces (CS−) were never paired with shock. While they failed to observe an overall increase in SCR for the CS+ versus the CS−, Petrovic and colleagues [21] observed greater conditioning related increases in SCR from the second half of the experiment compared to the first half of the experiment that were positively correlated with BOLD activation in the bilateral amygdala, using a region of interest (ROI) approach focused on the amygdala and the fusiform gyrus, a region involved in face processing.…”
Section: 0 Introductionmentioning
confidence: 99%
See 1 more Smart Citation